Economic benefits of combining self-consumption enhancement with frequency restoration reserves provision by photovoltaic-battery systems. (1st August 2018) - Litjens, G.B.M.A.; Worrell, E.; van Sark, W.G.J.H.M.
Highlights: Development and comparison of six battery storage dispatch strategies. Strategies applied on 48 residential and 42 commercial PV battery systems. Limited reduction of self-consumption combined with large increase in profitability. Provision of frequency restoration reserves is recommended for profitable investments. Abstract: Residential and commercial photovoltaic (PV) battery systems are increasingly being deployed for local storage of excess produced PV energy. However, battery systems aimed at increasing self-consumption are not constantly put to use. Additional battery storage capacity is available for a second application to improve the profitability of an energy storage system. One of these options is the provision of frequency restoration reserves (FRR) to the electricity balancing market. This provision can be either negative to compensate for excess power supply, or positive to compensate for excess demand on the power market. This study assesses the benefits for residential and commercial PV-battery systems by combining PV energy storage for higher self-consumption with provision of FRR. Six battery storage dispatch strategies were developed and assessed on the technical and economic performance of 48 residential and 42 commercial PV-battery systems. These systems were modelled over their economic lifetime with a time resolution of 5 min and with historical energy consumption measurements and market prices. FRR provision results in a small drop in the self-consumption rate of 0.5%. However annual revenues are significantly increased. Using battery storage systems only for self-consumption is not profitable with the assumptions used in this study. Provision of negative FRR substantially reduces the electricity bought with the consumption tariff and increases investment attractiveness substantially. Prioritizing the provision of FRR over self-consumption enhancement results in even higher revenues, but significantly reduces self-consumption. We recommend FRR provision to economically investment in residential battery storage systems. Commercial systems need prioritization of both positive and negative FRR provision over self-consumption for a cost-effective investment. In conclusion, combining enhancement of PV self-consumption with the provision of frequency restoration reserves leads to profitable investments.